Hatching Failure In Ex-Situ Nests Of Hawksbill Turtle (Eretmochelys Imbricata) In Melaka, Malaysia - See, Khai Wei (2022)
Hawksbill turtle (Eretmochelys imbricata, Linnaeus 1766) nesting in Melaka, Malaysia faces enormous pressures from various human activities along its coastline. The hatchery of the Department of Fisheries at Padang Kemunting, Melaka provides an important ex-situ conservation and management tool as threats such as egg poaching, inundation, and natural predation are prevalent at nesting beaches. Ex-situ conservation has been implicated in causing low hatching success to sea turtle nests. This study aims to identify the factors that contribute to hatching failure in ex-situ nests of hawksbill turtle using several approaches during three nesting seasons from 2018 to 2020, from 13 nesting beaches in Melaka. To analyse hatching success and egg mortality, post-emergence nest excavation was conducted on 241 clutches to determine the number of successfully hatched eggs and the stages of the unhatched eggs. The mean hatching success was 58.2 ± 28.2% (n = 241). Among the unhatched eggs (n = 9,872), 70.8% were undeveloped, 11.2% were in early embryonic stage, 1.1% were in mid embryonic stage, 6.3% were in late embryonic stage, 5.3% were depredated, and another 5.3% were decayed. Analysing eight potential determinants, only two variables were found to affect hatching success or egg mortality in this study, which were the incubation period and clutch size of the nests. The large number of undeveloped eggs led to the concern that the eggs were unfertilised. Egg fertility was determined using the white spot method conducted at the beginning of egg incubation on 50 clutches. The mean egg fertility was 85.9 ± 16.5% (n = 50), but the mean hatching success was significantly lower at 57.6 ± 24.3% (n = 50).